(untitled) (International relations and international law Journal, 2016)
Today, relationsbetween Chinaand the U.S.are in the spotlightof world politics.Since theirrecoveryin 1971,they were different – cooperative,competitive, and in recent years – carry-in relationshippotential adversaries.It is the efficiency of their bilateral cooperation and solves the current economic contradictions stability depends on the development of world economic relations. Interaction of China and the U.S. –it is not only the relationship between the different in strength and influence in the international arena, but also a clash of divergent ideas about themselves and the whole world. The relationship between U.S. and China are the strategic partnership relations, followed by a growing interdependence, where bilateral dialogue contributes to the comprehensive discussion and finding a solution to the current issues, such as trade imbalances and their possible causes.